Molecular Detection of PCV2 And PPV in Pigs in Republic of Srpska, Bosnia and Herzegovina - Lukač Bojan (Sciendo, 2016)
The presence of porcine circovirus 2 and porcine parvovirus was examined in forty clinical samples of spleen, lymph nodes and lungs originating from non-vaccinated swine by polymerase chain reaction. All animals were reared in extensive livestock farming systems in different geographical districts of Republic of Srpska, Bosnia and Herzegovina. Porcine circovirus 2 DNA was detected in four lymph node and two spleen samples (15%), while porcine parvovirus DNA was identified in five lymph node samples (12.5%). The presence of both viruses was detected in three lymph node samples (7.5%). Partial nucleotide sequence of ORF1 gene of 2 porcine circovirus 2 and VP2 gene of 2 porcine parvovirus isolates was determined. The nucleotide sequences of two PCV2 isolates from RS-BIH included in phylogenetic typing are similar and cluster together with the strain Mantova isolated from domestic pigs in Italy, strains DE006-14 and DE222-13 isolated from pigs in Germany as well as with the strain Jvnan isolated from pigs in China. Also, analyzed PCV2 isolates were partially similar to the strain NIV-C SRB isolated from pigs in Serbia. The nucleotide sequences of two PPV isolates that were included in phylogenetic typing showed a high level of similarity with the strain Challenge isolated from pigs in UK, strain Kresse isolated from pigs in USA and strains 77 and LZ isolated from pigs in China.